A screening model to predict microalgae biomass growth in photobioreactors and raceway ponds1. (17th January 2013) - Huesemann, M. H.; Van Wagenen, J.; Miller, T.; Chavis, A.; Hobbs, S.; Crowe, B.
Abstract A microalgae biomass growth model was developed for screening novel strains for their potential to exhibit high biomass productivities under nutrient‐replete conditions in photobioreactors or outdoor ponds. Growth is modeled by first estimating the light attenuation by biomass according to Beer‐Lambert's Law, and then calculating the specific growth rate in discretized culture volume slices that receive declining light intensities due to attenuation. The model uses only two physical and two species‐specific biological input parameters, all of which are relatively easy to determine: incident light intensity, culture depth, as well as the biomass light absorption coefficient and the specific growth rate as a function of light intensity. Roux bottle culture experiments were performed with Nannochloropsis salina at constant temperature (23°C) at six different incident light intensities (10, 25, 50, 100, 250, and 850 µmol/m2 s) to determine both the specific growth rate under non‐shading conditions and the biomass light absorption coefficient as a function of light intensity. The model was successful in predicting the biomass growth rate in these Roux bottle batch cultures during the light‐limited linear phase at different incident light intensities. Model predictions were moderately sensitive to minor variations in the values of input parameters. The model was also successful in predicting the growth performance of Chlorella sp. cultured in LED‐lighted 800 L raceway ponds operated in batch mode at constant temperature (30°C) and constant light intensity (1, 650 µmol/m2 s). Measurements of oxygen concentrations as a function of time demonstrated that following exposure to darkness, it takes at least 5 s for cells to initiate dark respiration. As a result, biomass loss due to dark respiration in the aphotic zone of a culture is unlikely to occur in highly mixed small‐scale photobioreactors where cells move rapidly in and out of the light. By contrast, as supported also by the growth model, biomass loss due to dark respiration occurs in the dark zones of the relatively less well‐mixed pond cultures. In addition to screening novel microalgae strains for high biomass productivities, the model can also be used for optimizing the pond design and operation. Additional research is needed to validate the biomass growth model for other microalgae species and for the more realistic case of fluctuating temperatures and light intensities observed in outdoor pond cultures. Biotechnol. Bioeng. 2013; 110: 1583–1594. © 2012 Wiley Periodicals, Inc.